Objective and Subjective Study of the Acoustical Characteristics of Auditorio 400 Designed by Jean Nouvel for the Museum Reina Sofia in Madrid. Issue 4 (December 2014) - del Cerro, Emiliano; Ortiz, Silvia Mª
The Auditorio 400 is a new auditorium located inside the National Museum "Centro de Arte Reina Sofia" in Madrid. It is the work of the renowned French architect Jean Nouvel. This hall has acoustic problems derived from its innovative style and from the use of its space for multiple events. For these reasons, an acoustical study was carried out in order to analyse these problems and to provide solutions to the deficiencies found without the need of large structural and aesthetics changes to the current design by Jean Nouvel. This paper presents the results of the sound pressure level measurements inside the hall, as well as a survey carried out to evaluate the location of the acoustic problems. Finally, the survey presents the interesting coincidences between objective measures and subjective opinions.